A Decade of Ethnomathematics Research (2015–2025): A Cross-Country Analysis of Global and Local Perspectives - Madu, Aleksius (Department of Mathematics Education Program IPI Garut, 2025)
Studi etnomatematika telah berkembang pesat sebagai sebuah disiplin ilmu yang meneliti hubungan antara matematika dan budaya di seluruh dunia. Artikel ini menyajikan perbandingan studi etnomatematika di berbagai negara, menyoroti perspektif global dan lokal yang mempengaruhi fokus penelitian, metodologi, dan implikasi pendidikan. Metode yang digunakan adalah metode tinjauan sistematis untuk mengumpulkan, mengevaluasi, dan mensintesis hasil penelitian terdahulu yang relevan dengan topik yang dikaji. Dengan menganalisis studi kasus dari beberapa wilayah geografis dan budaya, artikel ini mengidentifikasi pola umum dan perbedaan spesifik dalam praktik matematika budaya. Pemahaman komparatif ini diharapkan dapat memperkaya wawasan tentang universalitas dan partikularitas matematika serta membuka jalan bagi pengembangan kurikulum yang lebih relevan secara budaya dan inklusif baik di tingkat global maupun lokal. The study of ethnomathematics has grown rapidly as a discipline that examines the relationship between mathematics and cultures worldwide. This article presents a comparative analysis of ethnomathematics studies across different countries, highlighting the global and local perspectives that shape research focus, methodology, and educational implications. The method employed is a systematic review approach to collect, evaluate, and synthesize previous research results relevant to the topic under review. By analyzing case studies from several geographical regions and cultures, the article identifies common patterns and specific differences in cultural mathematical practices. This comparative understanding is expected to enrich insights into the universality and particularity of mathematics, paving the way for the development of more culturally relevant and inclusive curricula at both global and local levels.